The Secret of Happiness and Prevention of Family Relationships in Youth - Shahodat Khalikova (Euro Asian Journal Publishing, 2024)
The family is a unique institution of human interaction. This uniqueness lies in the fact that this closest union of several people (husband and wife, then children, and the parents of the husband or wife can live together with them) are bound by moral obligations. In this union, people strive to spend as much time as possible in joint interaction, to bring joy and pleasure to each other in the process of interaction
Keywords: relationships; family; prevention; counseling